Analisis Penentuan Pusat Pertumbuhan dalam Pengembangan Wilayah di Kabupaten Karo, Provinsi Sumatera Utara - SEMBIRING, ZOVANY RIMALEMNA BR; ANTARA, MADE; DEWI, IDA AYU LISTIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Analysis for Determining The Growth Poles in Regional Development in Karo Regency, North Sumatra Province The slowing pace of economic growth and the contribution disparity between sectors in Karo Regency show that more effort is needed in development in Karo Regency.  This study aims to analyze the economic sector classification of Karo Regency, determine potential districts as the growth poles, and analyze the interaction between potential districts as the growth poles and surrounding districts. This study uses secondary data collected through documentation. The indicators used are the regional GDP data of Karo Regency and North Sumatra Province in 2014-2018, infrastructure data, population quantity, and distance between districts in Karo Regency and analyzed by using klassen typology, scalogram, and gravity. Those in the developed sectors in Karo Regency were the public administration, defense, and compulsory social security sector, the education service sector, the health service and social activities sector, and other services sectors. Kabanjahe District and Berastagi District are potential districts as the growth poles in Karo Regency. Kabanjahe District has the closest interaction with Tigapanah District, while Berastagi District has the closest interaction with Merdeka District. Prioritizing the development of developed sectors without neglecting other sectors and determining the growth pole s can be considered as region al development efforts in Karo Regency.